2019
DOI: 10.1111/joor.12832
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous pain modulation assessed with offset analgesia is not impaired in chronic temporomandibular disorder pain patients

Abstract: Background: Abnormal endogenous pain modulation (EPM) was suggested as a pathophysiological characteristic of chronic pain. EPM has been investigated using psychophysical tests for pain facilitation and inhibition such as temporal summation of pain and conditioned pain modulation, respectively. Another psychophysical test for pain inhibition is offset analgesia (OA), where small variations in noxious stimulus intensity over time elicit a disproportionately large analgesic response. OA has been investigated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Studies have shown that cold pain (Nissen et al, 2018) and isometric exercise (Harris et al, 2018) did not affect OA when measured at a remote test site. Interestingly, even in patients with chronic temporomandibular disorder, another trigeminal pathology, the OA response was normal, but again, the measurement was performed outside of the trigeminal system (Moana-Filho et al, 2019). These results can be explained by different methodological and analytical approaches.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown that cold pain (Nissen et al, 2018) and isometric exercise (Harris et al, 2018) did not affect OA when measured at a remote test site. Interestingly, even in patients with chronic temporomandibular disorder, another trigeminal pathology, the OA response was normal, but again, the measurement was performed outside of the trigeminal system (Moana-Filho et al, 2019). These results can be explained by different methodological and analytical approaches.…”
Section: Discussionmentioning
confidence: 97%
“…Other study supporting central amplification of pain in PDAP patients showed greater activation in brain regions related to the sensory‐discriminative and cognitive components of pain perception in patients relative to pain‐free controls following matched dentoalveolar pressure intensity stimulation during functional magnetic resonance imaging (Moana‐Filho, Bereiter, & Nixdorf, ). Put together, these findings suggest dysfunction of endogenous pain modulation mechanisms and brain‐related pain amplification following dentoalveolar mechanical painful stimulus (Moana‐Filho et al, ; Nasri‐Heir et al, ) similarly to other proposed COPCs such as TMD (Moana‐Filho, Herrero Babiloni, & Nisley, ; Moana‐Filho, Herrero Babiloni, & Theis‐Mahon, ) and fibromyalgia (O'Brien, Deitos, Trinanes Pego, Fregni, & Carrillo‐de‐la‐Pena, ; Sawaddiruk, Paiboonworachat, Chattipakorn, & Chattipakorn, ).…”
Section: Can Be Pdap Considered a Copc?mentioning
confidence: 70%
“…Data reported here were collected as part of a parent study conducted at the University of Minnesota School of Dentistry (UMN SOD) assessing somatosensory characteristics and neuroimaging outcomes from participants with chronic TMD pain and pain-free controls 44 , 45 . Of the 52 female participants enrolled in the parent study, five had partial data missing which prevented them to be considered for the present study.…”
Section: Methodsmentioning
confidence: 99%
“…All participants were informed in detail about the experimental protocol and gave oral and written informed consent before entering the study. Full description of the experimental protocol can be found elsewhere 44 , 45 . Briefly, data were collected during three experimental visits, each of them separated by a 2–4 day period which is defined here as “short-term”.…”
Section: Methodsmentioning
confidence: 99%